Antimicrobial Resistance in Sexually Transmitted Infections: Current Trends - A. A. Khryanin (Антибиотики и Химиотерапия)
The review article discusses current trends in antibiotic resistance in bacterial and protozoal sexually transmitted infections (STIs). Antimicrobial resistance in STIs has increased significantly in recent decades due to the overuse and misuse of antibiotics, fueled by population migration and the high incidence of STIs worldwide. While emerging cephalosporin-resistant strains of Neisseria gonorrhoeae are one of the most pressing problems in the world, other pathogenic STIs that are resistant to antibiotics, such as Mycoplasma genitalium and Chlamydia trachomatis, are increasingly being reported. The emergence of multidrugresistant strains of bacterial STIs is of particular concern for researchers. The emerging global crisis in STI treatment is the result of neglect and inattention to repeated warnings from researchers about the emergence of STI strains resistant to the existing antibiotics, as well as shifting priorities in the pharmaceutical industry, which limited the development of new antibiotics. The current antimicrobial portfolio does not provide cause for optimism, as it contains few new antibiotics, and most developments are in the early stages of clinical trials. Experts have suggested that the failure of existing STI treatment regimens is largely inevitable and have called for the creation of entirely new classes of antimicrobial drugs that would take decades to develop. Currently, there are several promising alternative strategies for the treatment of antibiotic-resistant STIs. The use of phage therapy, antimicrobial peptides, and hydrolytic enzymes are particularly promising directions.